2002
DOI: 10.1002/bies.10113
|View full text |Cite
|
Sign up to set email alerts
|

Is human aging still mysterious enough to be left only to scientists?

Abstract: The feasibility of reversing human aging within a matter of decades has traditionally been dismissed by all professional biogerontologists, on the grounds that not only is aging still poorly understood, but also many of those aspects that we do understand are not reversible by any current or foreseeable therapeutic regimen. This broad consensus has recently been challenged by the publication, by five respected experimentalists in diverse subfields of biogerontology together with three of the present authors, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 64 publications
0
32
0
Order By: Relevance
“…They react primarily to anti-aging interventions like regenerative medicine, stem-cell therapies, telomerase and efforts to mimic the effects of caloric reduction [20,21,22,23]. Other authours suggest that in order to maximise the benefits associated with eHealth interventions and their potential to improve the health sector whilst minimising their risks, eHealth technologies should be evaluated during all their life course: during design, development and deployment stages [24].…”
Section: Population Ageing and E-health Developmentsmentioning
confidence: 99%
“…They react primarily to anti-aging interventions like regenerative medicine, stem-cell therapies, telomerase and efforts to mimic the effects of caloric reduction [20,21,22,23]. Other authours suggest that in order to maximise the benefits associated with eHealth interventions and their potential to improve the health sector whilst minimising their risks, eHealth technologies should be evaluated during all their life course: during design, development and deployment stages [24].…”
Section: Population Ageing and E-health Developmentsmentioning
confidence: 99%
“…Growing expansion of so-called antiaging remedies promoted by a variety of companies promising increased human longevity induced hot debate on antiaging medicine in the scientific community (29,45,46). Discussing what is known about the possibility of slowing, stopping, or reversing aging in animals and how this might be applied to humans, Butler et al (29) concluded that there is no convincing evidence that the administration of any specific compound, natural or artificial, can globally slow aging in people, or even in mice and rats (29).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, there are already signs of a potential division of humanity into the biotechnologically-modified haves and the unengineered have-nots. In a recent issue of this journal, (2) several biogerontologists urged that the time is ripe to begin research on the reversal of human ageing (and see correspondence Ref.…”
Section: Bioessays 252 97mentioning
confidence: 99%